2022
DOI: 10.3390/ijms231810235
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α and IL-1β Modulate Blood-Brain Barrier Permeability and Decrease Amyloid-β Peptide Efflux in a Human Blood-Brain Barrier Model

Abstract: The blood-brain barrier (BBB) is a selective barrier and a functional gatekeeper for the central nervous system (CNS), essential for maintaining brain homeostasis. The BBB is composed of specialized brain endothelial cells (BECs) lining the brain capillaries. The tight junctions formed by BECs regulate paracellular transport, whereas transcellular transport is regulated by specialized transporters, pumps and receptors. Cytokine-induced neuroinflammation, such as the tumor necrosis factor-α (TNF-α) and interleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 82 publications
2
32
0
Order By: Relevance
“…It is known that lung infection or injury is associated with various neurological complications, from altered memory to cognitive decline (5154). In our model, even in the absence of direct penetration of PA into the brain, infected mice developed anxiety-like behaviors, which might result from cerebral microvascular dysfunction, BBB leakage, and systemic/local production of cytotoxic cytokines like IL-1β (5557) and TNF-α (47, 58) as previously documented.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…It is known that lung infection or injury is associated with various neurological complications, from altered memory to cognitive decline (5154). In our model, even in the absence of direct penetration of PA into the brain, infected mice developed anxiety-like behaviors, which might result from cerebral microvascular dysfunction, BBB leakage, and systemic/local production of cytotoxic cytokines like IL-1β (5557) and TNF-α (47, 58) as previously documented.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, previous studies have demonstrated a correlation between in vivo administration of proinflammatory cytokines and BBB leakage (39,43). The ability of cytokines to open the paracellular pathway of endothelial barrier has been attributed to endothelial cytoskeleton reorganization (24) and/or downregulation of junction protein expression (22,40,(44)(45)(46)(47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have demonstrated a correlation between in vivo administration of pro-in ammatory cytokines and BBB leakage (39,43). The ability of cytokines to open the paracellular pathway of endothelial barrier has been attributed to endothelial cytoskeleton reorganization (24) and/or downregulation of junction protein expression (22,40,(44)(45)(46)(47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first time that similar effects have been reported in HBP. In the endothelial cells of the BBB, we and others have reported that TNFα decreases ABCB1 and ABCG2 expression and functionality, thus suggesting different mechanisms of regulation in these cell types [ 48 , 64 ]. We have previously reported the upregulation of ABCB1 when the LXR signaling pathway is activated by natural or synthetic agonist in endothelial BBB cells [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…When ready, HBP were rinsed once with warm DMEM/HG/0.1% BSA and then incubated in DMEM/HG/0.1% BSA supplemented or not with 5 or 10 ng/mL of TNFα. These concentrations were selected based on previous in vitro studies published by us and others [ 64 , 65 , 66 , 67 ].…”
Section: Methodsmentioning
confidence: 99%